2017
DOI: 10.1097/ccm.0000000000002514
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Imputation of Pao 2/Fio 2 From Spo 2/Fio 2 Among Mechanically Ventilated Patients in the ICU: A Prospective, Observational Study

Abstract: Objectives In the contemporary intensive care unit (ICU), mechanically ventilated patients may not have arterial blood gas (ABG) measurements available at relevant timepoints. Severity criteria often depend on ABG results. Retrospective studies suggest that non-linear imputation of PaO2/FIO2 from SpO2/FIO2 is accurate, but this has not been established prospectively among mechanically ventilated ICU patients. The objective was to validate the superiority of non-linear imputation of PaO2/FIO2 among mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 25 publications
1
92
0
1
Order By: Relevance
“…For the SOFA score calculation, if a value was missing, we carried forward the value from the prior measurement. For LIS and SOFA score calculations, when PaO 2 / FiO 2 was not available, the PaO 2 was estimated from the SpO 2 using nonlinear imputation, and the SpO 2 / FiO 2 equivalent was used as described previously (64,65). For the cardiovascular dysfunction component of the SOFA score, patients on phenylephrine and vasopressin were scored using estimated norepinephrine equivalences based on prior studies (66,67).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…For the SOFA score calculation, if a value was missing, we carried forward the value from the prior measurement. For LIS and SOFA score calculations, when PaO 2 / FiO 2 was not available, the PaO 2 was estimated from the SpO 2 using nonlinear imputation, and the SpO 2 / FiO 2 equivalent was used as described previously (64,65). For the cardiovascular dysfunction component of the SOFA score, patients on phenylephrine and vasopressin were scored using estimated norepinephrine equivalences based on prior studies (66,67).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Subjects who no longer required mechanical ventilation were scored 0 for the respiratory component of the SOFA score, as the PaO 2 /FiO 2 ratio was either unavailable or could not be reliably compared with the PaO 2 /FiO 2 ratio in mechanically ventilated subjects. SpO 2 /FiO 2 was not used to impute the PaO 2 /FiO 2 ratio in subjects no longer requiring mechanical ventilation, as this methodology has only been validated in mechanically ventilated ARDS patients (64,65).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…Through the help of noninvasive pulse oximetry, clinicians can obtain SpO 2 and calculate the SpO 2 /FiO 2 ratio, which has been demonstrated to be well correlated with the PaO 2 /FiO 2 ratio among patients with mechanical ventilation and ARDS after using a nonlinear imputation strategy [ 10 , 11 ]. Moreover, DesPrez et al showed that oxygenation saturation index (OSI) combining the SpO 2 /FiO 2 ratio and mean airway pressure was well correlated with the oxygenation index (OI) and could be a reliable predictor of ARDS patients’ outcome [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some pathophysiological factors, including lung resection, pulmonary vessels obstruction, and higher positive end-expiratory pressure, may potentially generate the trust-less data of EVLWI [14]. PaO2/FiO2 and Lac widely veri ed in the multiple intensive care scenarios [15][16][17], likewise present the affordable alternatives to invasive methods in our results, especially combined both themselves.…”
Section: Discussionmentioning
confidence: 74%